Band-gap engineering of BiOCl with oxygen vacancies for efficient photooxidation properties under visible-light irradiation. Issue 5 (17th January 2018) - Cui, Dandan; Wang, Liang; Xu, Kang; Ren, Long; Wang, Li; Yu, Youxing; Du, Yi; Hao, Weichang
Abstract : Engineering the electronic structure of BiOCl through the creation of oxygen vacancies can be a good strategy to enhance the photooxidation activity of BiOCl. Abstract : It remains a great challenge to understand the role of oxygen vacancies in determining the photooxidation properties of semiconductors under visible-light irradiation. Herein, BiOCl with oxygen vacancies is proposed as an excellent model to study the relationship between oxygen vacancies and photooxidation properties. BiOCl nanosheets with abundant oxygen vacancies are synthesized via a facile solvothermal route. Theoretical and experimental results reveal that after the introduction of oxygen vacancies, a new electron donor level appears in the band gap of BiOCl, extending the absorption from the ultraviolet to the visible regime. As expected, BiOCl nanosheets with oxygen vacancies exhibit visible-light-driven photocatalytic activity towards oxygen evolution. In addition, BiOCl with abundant oxygen vacancies exhibits a higher visible-light photocurrent and more efficient photoinduced charge separation and transportation than BiOCl with a small number of oxygen vacancies. The introduction of oxygen vacancies on the surfaces of semiconductors provides a promising way to improve the visible-light photooxidation activity of photocatalysts.